Critical issues for the future of the Australian urban water supply industry - Fazakerley, Victor William (Curtin University, 2005)
This study makes a contribution to the Australian urban water supply industry because it highlights some of the critical issues the industry faces in the future. Through the scenarios it illuminates an alternative method to develop strategies for the future. Ultimately the end result of scenario planning is not a more accurate picture of the future, but better decision making for the future. This is a significant piece of research because it demonstrates the advantages of the scenario planning process as a method to illuminate the potential future dangers and opportunities in the water industry's business environment. The scenarios can be used as a launching pad for strategic planning and to prepare the water industry for the uncertainties it faces. Water is precious and essential to life. Water supply is arguably the ultimate essential service. Australia uses about 22,000 gigalitres of water [l gigalitre (GL) = 1,000,000,000 litres, approximately 444 Olympic swimming pools (ABS 2004)] per annum across all sectors, irrigation, industry and domestic. The aim of this study was to determine the critical issues for the future of the Australian urban water supply industry. The study achieved this with the aid of scenarios that tell stories about urban water supply to the year 2025. A key to this study is the concept of organisations as living organisms, which are capable of learning and adapting to changes in their business environment. Today's business environment is constantly changing through globalisation, technological innovation and society's values. To survive, organisations must be able to anticipate and adapt to this often uncertain environment.Traditional methods, from a mechanistic perspective, of developing strategic plans for the future have a poor track record because they invariably rely on forecasting and predicting the future from historical information that, in an increasingly uncertain and fast changing world, may no longer be appropriate. Scenarios are stories about the future. They combine uncertainty and trends with creativity, insight and intuition to enable an organisation to learn and develop strategies for the future from an organic perspective. Scenarios are not predictions, but they are plausible stories about the future. The stories do allow an organisation to re-perceive a different world by questioning prevailing paradigms and assumptions. The underlying philosophical basis for scenario planning is constructivist which is consistent with the ontological position taken for this study. This study was undertaken under a qualitative research paradigm. The ontological position taken to answer the research question was constructivist with a critical perspective where realities are intangible mental constructs based on the culture and experience of individuals or groups. Constructs are more or less informed and changeable. From an epistemological perspective the constructivist position assumes that the enquirer and subject of the research are interactively linked so that findings are created. Research under a constructivist paradigm requires a hermeneutical and dialectical methodology leading to interpretation.The methodology adopted for this study was grounded research, being a modification of grounded theory and applicable to the business environment. Data were initially gathered by semi-structured interview, the objective being two fold. 1. The data were used to elicit critical issues for the future of the Australian urban water supply industry. 2. The data were used to develop 'plausible' futures for the urban water supply industry in the form of scenarios. The data were analysed using grounded research principles and organised using NVivo (Richards 1999; NVivo 2002). After two stages of analysis, 16 major categories, focusing on the future emerged from the data. In order to write the scenarios two key uncertainties critical to the future of the urban water supply industry were required for the scenario matrix. The two selected were 'Water availability' and 'Technological change' from the water industry's contextual environment. These two key uncertainties were considered to be the most uncertain and have the greatest impact on the future of the water industry. These two key uncertainties formed the context for the scenarios into which over 200 other issues were de-dimentionalised, as in the scenario planning method, and crafted into four scenarios. A time horizon of 2025 was selected for the scenarios to reflect the water industry's long term planning horizon.The scenarios were called 'Decadent water use', which depicts a future where there is plenty of water and technology addresses the cost of service delivery; 'Smart water world', which depicts a future where water is scarce but is addressed by technology providing alternative sources of water; 'Muddy waters', which depicts a future where there is plenty of water but technology does not address the cost of delivery and issues of infrastructure deterioration and 'Mad Max water world', which depicts a future where water is scarce and technology does not address the scarcity, the situation becomes a crisis. From the scenarios and using concepts from complex adaptive systems theory a number of critical issues emerged from the data. Some were at a philosophical level such as whether water, as a common good, fits with society's philosophy about water. Others were at a practical level for example expressing the criticality for the water industry to build community trust and support. The research notes the potential for further qualitative research in the fields of community attitudes and behaviours towards water, water services, recycling wastewater and the preparedness to pay for water services. In addition there is potential to further develop scenarios presented in this study; 'Decadent water use', 'Smart water world', 'Muddy waters' and 'Mad Max water world'; for the Australian urban water supply industry using the data from this research as a basis for group consultation.